The Twits - "Dahl, Roald" (Puffin Books London, 2016)
The Twits is a darkly humorous children$1 (Bs book by Roald Dahl, featuring a grotesque married couple, Mr. and Mrs. Twit, who delight in playing cruel pranks on each other and tormenting animals. Through clever writing and exaggerated characters, Dahl explores themes of cruelty, ugliness (both physical and moral), and poetic justice. The story ultimately champions kindness and intelligence as the monkeys and birds, victims of the Twits' abuse, outwit them with the help of a clever bird named the Roly-Poly Bird. The book uses humor and satire to deliver moral lessons in a way that captivates young readers.s
Keywords: Justice and Revenge